Philosophy and Secularization: An Approximation to «Obedience» as «Form» of Thought - Llinás Puente, Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
If philosophy in a time of total secularization consists of a general declaration of disobedience to any essential instance, the philosophy that is never totally secularized–maybe the only historically existent philosophy–should be based on a recognition of obedience as a structural element of philosophical thought.